Stem Cell Therapy in Acute Coronary Syndrome - Rajbhandari, Rajib (Nepalese Heart Journal, 2006)
Acule coronary syndrome and congestive heart failure are still among challenging problems in the field of cardiovascular medicine despite many advances in the field. Stem cell therapy has come as a new hope and a promise for the hopeless.